Effect of saline stress on the activity of some antioxidant enzymes and their gene expression in potato plants (Damascus University Journal of agriculture sciences, 2021)
This research was carried out to study the changes in the activity of some antioxidant enzymes (superoxide dismutase SOD, catalase CAT and ascorbate peroxidase APX) and the gene expression of some genes encoded these enzymes (iron-superoxide dismutase I-SOD, copper-zinc-superoxide dismutase CuZn-SOD, catalase-1 CAT1, catalase-2 CAT2, cytoplasmic ascorbate peroxidase APXcyto and chloroplastic ascorbate peroxidase APXt) in potato cultivar Amarin cultivated in-vitro under the effect of different concentrations of salinity (0, 50, 100, 150 and 200 mM of NaCl). Saline stress increased the activity of all studied antioxidant enzymes at medium salinity concentrations (100 and 150 mM) and decreased it at high concentration (200 mmol). This change in the activity of enzymes coincided with the change in the expression of the genes responsible for these enzymes, the expression of these genes increased at low and medium salinity concentrations and decreased at high salinity concentrations. Thus, antioxidant enzymes play an important role in the defense mechanisms of potato plants in salt-stressed environments.
Keywords: Potatoes; saline stress; oxidative stress; antioxidant enzymes; gene expression